2013
DOI: 10.1016/j.pec.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Patient-health care provider communication among patients with newly diagnosed prostate cancer: Findings from a population-based survey

Abstract: Objective To examine the multidimensional concept of patient-health care provider (HCP) communication, its effects on patient satisfaction with oncology care services, and related racial differences. Methods The current analysis draws from a population-based survey sample of 1011 African American and 1034 Caucasian American men with newly diagnosed prostate cancer. The variables of satisfaction with health care services, interpersonal treatment, contextual knowledge of the patient, and prostate cancer commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
(50 reference statements)
0
27
0
Order By: Relevance
“…The measurement model presented in the previously published paper 37 fit the reduced dataset for this analysis (Chi-square = 4.294, df = 2, p = 0.1169; RMSEA = 0.035, 90%CI = (0.000, 0.082); CFI / TLI = 0.999 / 0.997). No modification indices indicated that the model could be improved by relaxing restrictions (data not shown).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The measurement model presented in the previously published paper 37 fit the reduced dataset for this analysis (Chi-square = 4.294, df = 2, p = 0.1169; RMSEA = 0.035, 90%CI = (0.000, 0.082); CFI / TLI = 0.999 / 0.997). No modification indices indicated that the model could be improved by relaxing restrictions (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…37 Prostate cancer communication refers to the instructions and advice about prostate cancer symptoms, treatment, decision-making about care, and treatment-related side-effects. 38 Contextual knowledge of the patient refers to the patient’s evaluation of the degree to which health care providers have knowledge of the participant’s general life.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Song et al . ). This is especially true for oncology nursing, a highly demanding nursing subfield that requires up‐to‐date knowledge, good interpersonal and problem‐solving skills, and superb primary care skills (Akin & Erdogan ; Granda‐Cameron et al .…”
Section: Introductionmentioning
confidence: 97%
“…Research-to-date has analyzed real time recordings of medical encounters about physicians’ communication behaviors and the clinical visit structure within the context of treatment decision-making for prostate cancer [26,27] or used self-reported data collected from patients after treatment decisions were made [16,2831]. Effective and competent physician-directed communication constitutes only one of the core communication dimensions in cancer care [32]; patients and their family members also participate in the consultation and play a role in communication that is equally important to that of the providers.…”
Section: Introductionmentioning
confidence: 99%